The Important Role of Government for Spatial Planning in A Sustainable Development Perspective - Himatul Aliyah; Frensiska Ardhiyaningrum; Luthfi Nur Azizah; Maulia Nurfadillah; Marshela Alviani (Universitas Muhammadiyah Surakarta, 2024)
Law enforcement regarding spatial planning errors, namely the regeneration of the spatial planning atlas, is very important. The law enforcement process is the most common problem encountered when carrying out spatial planning, because too many spatial planning violations are allowed. The impact was that the spatial plan was changed because this violation was legalized. In realizing sustainable development goals in Indonesia, it is necessary to have a relationship between nature, a group of residents, and area managers in spatial planning in order to increase welfare in society. The problem taken in this study is how to implement spatial planning and achieve sustainable development. Based on Law No. 26 of 2007 concerning Spatial Planning, normative juridical techniques with descriptive analysis can conclude that there are inconsistencies in law enforcement regarding deviations in spatial planning, and the sanctions given are not commensurate with the mistakes committed.